(3TQM GdQSGdI GdTeSjIs - (3Ydj Hf YeQ Hf Ydj GdcGJHj GdbRhjfj, fLe GdOjf, hjbGd dg OHjQGf,J (B675 (3g` s ((3YHOGdaJGM Hf CMeO CHhGdEbHGd GdNhGfci s)
(3ChdgG (B:s
(3hHYO abO WGd CdMGM GdeTJZdjf Ydi GdeJQOOjf Edi Cf CTQM GdQSGdI GdTeSjI s
(3BNQgG (B:s
(3Cf jchf LRA GdTF eWdhH HGdHQgGf dGf GdGLRGHjI GdKHhJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdTeSjI GfXQ cTa GdXfhf L (B2 (3U` (B1063s
(3GjVGM Gdecfhf L (B2 (3U` (B56s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdadSaI hGdefWbs